Adobe Photoshop elements : advanced editing techniques and tricks - Padova, Ted (New Riders, 2022)
Adobe Photoshop Elements Advanced Editing Techniques and Tricks: The Essential Guide to Going Beyond Guided Edits is a must for those who want to go beyond automated features and Guided Edits and delve into the many advanced techniques that are possible using Adobe Photoshop Elements. LEARN HOW TO Perfect editing portrait images by performing techniques such as skin tone correction, frequency separations, skin smoothing, and enhancing facial features Properly edit and enhance a subjects eyes, lips, eyebrows, and facial lighting Apply advanced photo compositing techniques, utilizing rules for controlling perspective Use color grading techniques similar to those used by professional motion picture film editors Delve into advanced tools not included in Photoshop Elements such as curves, color range, selective color, working with color LUTs, and more With detailed step-by-step instructions, this book is targeted to intermediate and advanced users who want to take their photography to the next level. Additional tips using Photoshop Elements can be found on Teds YouTube channel at www.YouTube/tedpadova.